PENGARUH REPUTASI PERUSAHAAN RENTAL DAN RELATIONSHIP VALUE TERHADAP KEPERCAYAAN DAN KOMITMEN SERTA LOYALITAS PERUSAHAAN PENGGUNA JASA PERSEWAAN KENDARAAN DI PROVINSI KALIMANTAN TIMUR - Novel Reonald (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2017)
The purpose of this study is to examine the influence of vehicle leasing company (lessor) reputation and relationship value on loyalty of vehicle user company (lessee) through trust and commitment of lessee in car rental industry. The conceptual framework of the study consists of the following constructs: reputation, relationship value, trust, commitment, and loyalty. Moreover, 9 hypotheses were developed and tested. Loading factor and construct reliability were used to test the validity and reliability of the instrument. A total of 172 questionnaires were returned completely from companies using leased cars in East Kalimantan by e-mail then they processed using SEM analysis techniques for hypotheses testing. Strong support was found for 8 of the 9 hypotheses. Findings reveal that 1. Reputation had significant influence on trust, 2. Reputation had significant influence on commitment, 3. Reputation had no significant influence on loyalty, 4. Relationship value had significant influence on loyalty, 5. Relationship value had significant influence on trust, 6. Relationship value had significant influence on commitment, 7. Trust had significant influence on commitment, 8. Trust had significant influence on loyalty, 9. Commitment had significant influence on loyalty. This study worked within the domain of B2B relationship service marketing. This study showed that the reputation of a good provider did not always have an influence on customer loyalty. Therefore, providers need to increase relationship value, trust and commitment that have been proven influence customer loyalty, either directly or indirectly.